Plantation Women and Children: Recruitment Policies, Wages and Working Conditions of Javanese Contract Labourers in Sumatra, c. 1870-1940 - Teeuwen, Danielle (TSEG - The Low Countries Journal of Social and Economic History, 2022)
In the period 1870-1940 over a million Javanese labourers travelled to Sumatra hoping for a better life. Although the literature focuses on the labour activities, working conditions, and wages of male workers, especially from 1900 onwards a substantial part of the hired labourers were women and children. This paper argues that in the late colonial period attempts were made to improve the conditions for family life on the plantations. These policies were aimed at creating a stable pool of workers in a context of widespread labour scarcity. However, improvements were slow, and when a labour surplus occurred during the Great Depression, women’s wages and contracts were affected most, which shows the gendered labour policies on the plantations were very much driven by an economic rationale.